An investigation of ultra-precision manufacturing methods in generating functional rectangular microstructures on the polymer material of polyimide - Jie Liu; Sheng Wang; Yingdong Huo; Qingliang Zhao; Xingyu Wang; Jiating Zhang (Journal of Materials Research and Technology)
Polyimide with surface microstructures have a significant applications in fields such as electronics and aerospace. Appropriate processing methods playing a crucial role in achieving high-quality microstructures to meet the above application requirements. In this study, rectangular microstructures were fabricated on polyimide surfaces using ultra-precision ordinary planing (UPOP), ultrasonic elliptical vibration cutting (UEVC), and utra-precision fly-cutting (UPFC) methods, and both theoretical and experimental investigations were conducted. The characteristics of the three processing methods were analyzed, establishing the relationship between the chips, and evaluating the surface quality of the microstructures, cutting forces, and chip morphology. The results indicate that, compared to UPOP, UEVC can improve the processing quality of microstructures. At a cutting depth of 35 μm, the edge defects of microstructure grooves processed by UEVC are 39 μm smaller, and the burr height is approximately 5 μm lower than that of UPOP. However, when the cutting depth is greater than or equal to 70 μm, the burr height for UEVC is higher than that for UPOP, with the maximum difference being around 15 μm. The UPFC method achieves the best surface quality for microstructures and demonstrates significant effectiveness in suppressing burr formation. Burr height is only measured to be approximately 4 μm at a cutting depth of 35 μm, and burrs are virtually undetectable at larger cutting depths. The maximum cutting force of UPOP is 4.81 N, while the maximum cutting force of UPFC is only 0.021 N, making the cutting force of UPOP 229 times that of UPFC. The chips produced by UPOP are primarily serrated, whereas the chips produced by UPFC consistently exhibit a slender, elongated shape. A small material removal rate and high slope can prevent chip interactions, thereby enabling the use of UPFC to manufacture high-quality PI microstructures.